2007
DOI: 10.1007/s10494-007-9069-3
|View full text |Cite
|
Sign up to set email alerts
|

The Flow Structure Produced by Pulsed-jet Vortex Generators in a Turbulent Boundary Layer in an Adverse Pressure Gradient

Abstract: The effect of pulsed jet vortex generators on the structure of an adverse pressure gradient turbulent boundary layer flow was investigated. Two geometrically optimised vortex generator configurations were used, co-rotating and counterrotating. The duty cycle and pulse frequency were both varied and measurements of the skin friction (using hot films) and flow structure (using stereo PIV) were performed downstream of the actuators. The augmentation of the mean wall shear stress was found to be dependent on the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 25 publications
1
13
0
1
Order By: Relevance
“…Hence, the structures produced at the highest pulse frequency could be considered quasi-steady. This has recently been observed in PIV measurements of the same flow by Kostas et al [17]. A plot of the intensity of the wall shear stress fluctuations (τ /τ ) as a function of duty cycle for each configuration and pulse actuation frequency is shown in Fig.…”
Section: Fluctuating Shear Stresssupporting
confidence: 74%
See 2 more Smart Citations
“…Hence, the structures produced at the highest pulse frequency could be considered quasi-steady. This has recently been observed in PIV measurements of the same flow by Kostas et al [17]. A plot of the intensity of the wall shear stress fluctuations (τ /τ ) as a function of duty cycle for each configuration and pulse actuation frequency is shown in Fig.…”
Section: Fluctuating Shear Stresssupporting
confidence: 74%
“…It is important to note that this result is based upon the measurement of the mean wall shear stress far downstream of the actuators. The development of structures and subsequent effect on other flow quantities close to the actuators has been shown to be different for pulsed and continuous jets, especially during the transient phases of the pulse cycle [17].…”
Section: Mass Flow Dependencementioning
confidence: 99%
See 1 more Smart Citation
“…The passive control methods delay the flow separation in the retreating region through the blade geometrical modification and are always in operation, regardless of need or performance penalty. Passive control devices such as Pulse Vortex Generator Jets (PVGJs) [15][16][17], Direct Synthetic Jet (DSJ) [18,19], Rod Vortex Generator (RVG) [20] and Vortex Trap Concept [21][22][23]were designed to generate vortices to reduce flow separation of the retreating blade at a high angle of attack. On the other hand, the second method controls flow by adding energy or momentum to the flow in a regulated manner.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few decades VGs have been widely researched and new concepts of non-solid VGs-such as synthetic jets or pulsed jets (Lin 2002;Wiltse and Glezer 1993;Amitay et al 1998;McManus et al 1994;Kostas et al 2007)-have been proposed. It has been demonstrated that active VGs provide similar benefits as passive VGs, but with a major added advantage: when they are not functional, there is no increment in the parasitic drag (Paul et al 2013).…”
Section: Introductionmentioning
confidence: 99%